2007
DOI: 10.1097/ana.0b013e3181453851
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Disruption of the Blood Brain Barrier by Intracarotid Mannitol Injection During Transient Cerebral Hypoperfusion in Rabbits

Abstract: Fairly large volumes of intracarotid mannitol (20% to 25%) are required to disrupt the blood brain barrier (BBB), that is, 200 to 300 mL/30 s in humans or 10 mL/40 s in rabbits. During transient cerebral hypoperfusion blood flow to the rabbit brain is decreased to 0.2 to 0.3 mL/30 s. We therefore hypothesized that if the disruption of the BBB by intracarotid mannitol was primarily due to its osmotic effects, injection of 0.2 to 0.3 mL of mannitol during transient cerebral hypoperfusion will be sufficient to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…7 In parallel studies, we had observed that BBBD in rabbits with IA mannitol was highly variable. 11,12 Similar variability in the degree of BBBD has also been reported in human subjects. 13 Such variability could have a very significant impact on the delivery of chemotherapeutic drugs that require BBBD.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…7 In parallel studies, we had observed that BBBD in rabbits with IA mannitol was highly variable. 11,12 Similar variability in the degree of BBBD has also been reported in human subjects. 13 Such variability could have a very significant impact on the delivery of chemotherapeutic drugs that require BBBD.…”
Section: Introductionsupporting
confidence: 72%
“…One millilitres of ICG was injected by solenoid controlled pneumatic pump over 2 s. MTX, a water soluble chemotherapy agent, was selected as the drug, and 3 ml of 0.1% (1 mg∕ml) of MTX in normal saline (Sigma Aldridge Co., St. Louis, MO) was injected with an IVAC syringe pump in bolus mode over 30 s. Mannitol, warmed to 37°C and filtered through a 0.2 micrometer filter, was hand injected (25%, 0.25 ml∕kg∕s for 30 s) after it was determined that mechanical pumps were unable to reliably administer the IA dose of mannitol required for this experiment. 11 In the control group, equivalent intravenous volume of saline was injected instead of mannitol over the same time period.…”
Section: Tracer and Drug Doses And Deliverymentioning
confidence: 99%
“…Shi et al, (2002) and Gergely et al (2005). (Wang et al 2007;WU et al 2007;USCDC 2009;UN 2010), which include anticancer agents such as fatty acids poly saccharides, and ergosterol (Takaku et al 2001;Ren et al 2008;Koyyalamudi et al 2009);N,N,N-tris (hydrazinecarbonyl) phosphoric triamide, selenium and vaccenic acid (Shi et al 2002; Sosnovsky and Rao 2004; Gergely et al 2005;De Barros 2008;Mattila et al 2010); antihypercholesterol agents such as fatty acids, glycoproteins, sterols and vaccenic acid (Ey et al 2007;Borchers et al 2008;De Barros 2008); antimicrobial agents such as agaritine and alcohols (Janak, et al 2006;Nagadka, et al 2006;Roupas, et al 2010); anti-cardiovascular disease agents such as fatty acids, sterols and pyran derivative (SCB, 2007(SCB, -2010; human health supporting agent's such as fatty acids, sterols and sugar alcohols (Andersson and Gry 2004;Ji, et al 2006); immune enhancer agents such as fatty acids, glycoproteins, polysaccharides and sterols (UN, 2010);…”
Section: Methodsmentioning
confidence: 99%
“…Multifunctionality is a key advantage of the nanoparticle-based approach for the cancer-specific delivery of therapeutic or imaging agents. Targeted dual imagings (MRI and Near IR optical imaging) [65,81] and targeted multifunctional nanoparticles for imaging (MRI) and therapy (PDT) [55][56][57][58] have been investigated.…”
Section: Nanoparticle Platform(nanoplatform)mentioning
confidence: 99%